Higher triglyceride-glucose index and triglyceride glucose-body mass index protect against sarcopenia in Chinese middle-aged and older non-diabetic women: a cross-sectional study - Min Li; Ying Liu; Lei Gao; Yongli Zheng; Luyao Chen; Yan Wang; Wei Zhang (Frontiers in Public Health)
PurposeSarcopenia, an age-related complication, constitutes a major public health problem given the aging of the population. However, it is frequently overlooked and undertreated in mainstream practice. The study aimed to investigate the correlations between triglyceride-glucose (TyG) index and TyG-body mass index (BMI) and sarcopenia in non-diabetic middle-aged and older women and whether they would be helpful indicators of sarcopenia.Patients and methodsThis cross-sectional study was conducted in the Department of Endocrinology, Hebei Medical University Third Hospital. This study prospectively enrolled 460 non-diabetic postmenopausal women aged ≥50 years.ResultsAs TyG and TyG-BMI increased, the prevalence of sarcopenia decreased. In multivariate analysis, the TyG index and TyG-BMI index were inversely associated with sarcopenia (OR: 0.492; 95% CI: 0.256–0.944 and OR: 0.948; 95% CI: 0.934–0.962). Women in the fourth TyG-BMI quartiles showed decreased OR of 0.009 (95% CI: 0.001–0.072) for sarcopenia with respect to first quartiles after adjusting confounding factors. The area under the curve (AUC) for TyG index in the diagnosis of sarcopenia was 0.598 (95% CI: 0.529–0.666), while the AUC for TyG-BMI index was 0.858 (95% CI: 0.816–0.899).ConclusionHigher TyG index and TyG-BMI index protected against sarcopenia in non-diabetic middle-aged and older females. Moreover, the TyG-BMI index was a reliable and cost-efficient biomarker to predict sarcopenia.